The Relationship Between Religiosity and Happiness Among Students of the Pancasila and Civic Education Study Program at the Faculty of Teacher Training and Education, Pamulang University - Adam Sugiarto; Rachmatullah Rusli (Journal of Smart Pedagogy and Education, 2025)
Religiosity plays a pivotal role in shaping psychological well-being, particularly among university students facing academic pressures. This study investigates the relationship between religiosity and happiness in 50 undergraduates enrolled in the Pancasila and Civic Education (PPKN) program at Pamulang University, Indonesia. Employing a cross-sectional survey design, validated scales measured multidimensional religiosity including intrinsic orientation, religious practice, and spiritual experience and subjective happiness. Descriptive analysis indicated high religiosity (M = 3.92, SD = 0.48) and moderate happiness (M = 3.18, SD = 0.57). Simple linear regression revealed that overall religiosity significantly predicts happiness (β = 0.76, t = 2.29, p = 0.027), explaining 85.5% of variance in subjective well-being. Subscale analyses demonstrated that religious practice accounted for 65.6% of happiness variance, while spiritual experience explained 46.2%. Correlational results further showed a significant negative relationship between religiosity and academic stress (r = –0.412, p < 0.01), indicating that stronger religious engagement is associated with reduced stress. Qualitative feedback highlighted that 72% of participants experienced emotional comfort from digital da’wah resources, underscoring the modern extension of religious coping via technology. Findings align with Allport’s Religious Orientation Theory and Pargament’s Religious Coping framework, suggesting that both intrinsic belief and active practice foster resilience and life satisfaction. Implications for educational policy include integrating culturally responsive religious support such as positive religious coping workshops and curated digital da’wah content into student services to enhance psychological well-being. Future longitudinal and mixed-methods research should examine causal pathways and differential effects of digital versus communal religious engagement on student happiness and stress management.